Effect of Ease And Trustworthiness To Use E-Commerce for Purchasing Goods Online - Givan, Bryan; Wirawan, Rio; Andriawan, Deden; Aisyah, Nurul; Asep, Asep; Syah Putra, Arman (International Journal of Educational Research & Social Sciences, 2021)
The background in this research is to find out whether there is a relationship between the ease and trust of an e-commerce with customers who buy goods online, with this ease and trust whether purchasing goods online is increasing what are the factors that make sales increase and the variables that influence it, with the ease of using this e-commerce system and with a high level of trust, the public will be more confident shopping in an e-commerce media, because the seller provides the best service or has a very good product so that people buy with believe in the products they buy. The method used in this research is to use quantitative methods by conducting surveys to several customers who have used e-commerce media, is it easy and trustworthy in an e-commerce to increase sales, therefore, with the survey media, data is obtained primarily and the truth can be justified. With the ease and level of confidence about customers, shopping on an e-commerce can increase, with the increase, we can find out what variables can make customers shop more online, therefore variables must be known by sellers with an e-commerce system, with known variables such as ease of trust and the presence of a low price level, product sales will increase. This research will produce data that can determine whether there is a relationship between convenience and trust in purchasing goods online, with this data it can be used as a basis for further research and can be the basis for developing e-commerce systems today.